The Significance of Mentorship in Enhancing the Implementation of the Waqf Core Principle: Case study of Harapan Dhuafa - Emmy Hamidiyah; Aimatul Yumna; Dede Haris Sumarno; Hermanu Susilo; Raji Reza Ilahi; Nurkaib (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2025)
Abstract: The Waqf Core Principles Implementation Index (WCPII) wasdeveloped in 2021 by the Indonesia Waqf Board and Central Bank of Indonesiaas a standardized framework to assess the core activities, governance, and riskmanagement of waqf managers (nazir) in the country. This index is critical forensuring the effectiveness, transparency, and governance of waqf institutions. Theobjective of this study is to evaluate the significance of mentorship in enhancingthe implementation of the WCPII, focusing on Harapan Dhuafa, one of the nazhirorganizations in Banten, Indonesia. This study employs a case study approach byusing three stages of structure evaluation: pre assessment, intervention and postassessment. The intervention consists of a structured mentoring program aimingto build institutional capacity in line with WCPII criteria. The findings indicatethat, the intervention significantly improve the WCPII, including core activities,governance, and risk management. The study contributes to the body ofknowledge on institutional waqf governance and highlights mentorship as astrategic approach for capacity-building in waqf institutions.Keywords: Mentorship, Waqf Core Principles, Structured Evaluation.